Band 3–mediated Plasmodium vivax invasion is associated with transcriptional variation in PvTRAg genes - De Meulenaere, Katlijn; Prajapati, Surendra Kumar; Villasis, Elizabeth; Cuypers, Bart; Kattenberg, Johanna Helena; Kasian, Bernadine; Laman, Moses; Robinson, Leanne J.; Gamboa, Dionicia; Laukens, Kris; Rosanas-Urgell, Anna (Frontiers in Cellular and Infection Microbiology, 2022)
The Plasmodium vivax reticulocyte invasion process is still poorly understood, with only a few receptor-ligand interactions identified to date. Individuals with the Southeast Asian ovalocytosis (SAO) phenotype have a deletion in the band 3 protein on the surface of erythrocytes, and are reported to have a lower incidence of clinical P. vivax malaria. Based on this observation, band 3 has been put forward as a receptor for P. vivax invasion, although direct proof is still lacking. In this study, we combined functional ex vivo invasion assays and transcriptome sequencing to uncover a band 3–mediated invasion pathway in P. vivax and potential band 3 ligands. Invasion by P. vivax field isolates was 67%-71% lower in SAO reticulocytes compared with non-SAO reticulocytes. Reticulocyte invasion was decreased by 40% and 27%-31% when blocking with an anti-band 3 polyclonal antibody and a PvTRAg38 peptide, respectively. To identify new band 3 receptor candidates, we mRNA-sequenced schizont-stage isolates used in the invasion assays, and observed high transcriptional variability in multigene and invasion-related families. Transcriptomes of isolates with low or high dependency on band 3 for invasion were compared by differential expression analysis, which produced a list of band 3 ligand candidates with high representation of PvTRAg genes. Our ex vivo invasion assays have demonstrated that band 3 is a P. vivax invasion receptor and confirm previous in vitro studies showing binding between PvTRAg38 and band 3, although the lower and variable inhibition levels observed suggest the involvement of other ligands. By coupling transcriptomes and invasion phenotypes from the same isolates, we identified a list of band 3 ligand candidates, of which the overrepresented PvTRAg genes are the most promising for future research.